2023
DOI: 10.1371/journal.pone.0283901
|View full text |Cite
|
Sign up to set email alerts
|

Maternal educational level and preterm birth: Exploring inequalities in a hospital-based cohort study

Abstract: Preterm birth has been related to inequalities in maternal educational level, but the causal mechanism is not entirely known. Some factors associated with preterm birth and low educational level such as chronic medical conditions, pregnancy complications and related-health behaviours could have a mediation role in the pathway. This study aimed to evaluate the association between maternal educational level and preterm birth, analysing the mediation role of these factors. We performed a retrospective cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
2
4
1
Order By: Relevance
“…The current study demonstrated that mothers who completed junior high school had a reduced risk for preterm births. This is different from the findings of Wagura and colleagues (10) but similar to that of Spanish and Japanese cohort studies (34,35) which indicated that maternal lower All rights reserved. No reuse allowed without permission.…”
Section: Discussioncontrasting
confidence: 96%
“…The current study demonstrated that mothers who completed junior high school had a reduced risk for preterm births. This is different from the findings of Wagura and colleagues (10) but similar to that of Spanish and Japanese cohort studies (34,35) which indicated that maternal lower All rights reserved. No reuse allowed without permission.…”
Section: Discussioncontrasting
confidence: 96%
“…Preterm delivery (i.e. giving birth prematurely) 55 , which is a risk factor for neurodevelopmental conditions in the offspring [45][46][47] , showed significant genetic correlations with lower educational attainment (rg=-0.30 [-0.39, -0.21], p=2.3x10 -10 ), mirroring the epidemiological association 56 , and with neurodevelopmental conditions (rg=0.58 [0.18, 0.97], p=0.004) (Extended Data Figure 8A, Supplementary Table 9). Premature birth was also associated with lower PGSEA in DDD (Extended Data Figure 8B).…”
Section: Exploring the Role Of Prenatal Factorsmentioning
confidence: 70%
“…This is consistent with epidemiological studies that found an association between prematurity and poorer neurocognitive outcomes even after controlling for socioeconomic confounders 45,[73][74][75][76][77][78][79] . We found some evidence from Mendelian randomization that lower educational attainment is causally associated with preterm delivery (Extended Data Figure 9B; Supplementary Note 5); this may be because lower educational attainment is associated with several factors that increase the risk of preterm delivery in the mother (such as a short inter-pregnancy interval 80 , exposure to tobacco smoke during pregnancy 81,82 , and pre-eclampsia 56 ). We acknowledge that causal estimates from Mendelian Randomization analyses may be biased when using population-based GWASs, as we have done, so these findings should be considered tentative until confirmed using sufficiently well-powered within-family GWASs 32 .…”
Section: Discussionmentioning
confidence: 94%
“…Since in the VEPT sample, mothers were older and had fewer years of education; future studies should learn about the impact of these and other demographic factors on mother-infant interactive continuity, as found by past research (Granés et al, 2023).…”
Section: Discussionmentioning
confidence: 88%